2017
DOI: 10.1097/sla.0000000000002409
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Resetting Radiation Sensitivity in Rectal Cancer

Abstract: An integrated analysis of rectal cancer miRs may yield biomarkers of radioresistance and offer treatment targets for resensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Although gene therapy has brought hopes to NPC patients, it is still in its infancy due to the complex of gene interaction network. CAB39 (calcium-binding protein 39) is an activated factor of STE20 kinase that has been shown involved in the progression of various cancers, including hepatocellular carcinoma, 7 gastric cancer, 8 colorectal cancer, 9 , 10 pancreatic cancer 11 and glioma. 12 15 However, its role in NPC is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although gene therapy has brought hopes to NPC patients, it is still in its infancy due to the complex of gene interaction network. CAB39 (calcium-binding protein 39) is an activated factor of STE20 kinase that has been shown involved in the progression of various cancers, including hepatocellular carcinoma, 7 gastric cancer, 8 colorectal cancer, 9 , 10 pancreatic cancer 11 and glioma. 12 15 However, its role in NPC is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization was performed on frozen tumor sections as described in our previous studies 45 , 46 using a digoxigenin (DIG)-labeled miR-494 LNA probe (Exiqon). DIG was detected by an anti-DIG horseradish peroxidase antibody (Roche) and amplified using a TSA-Plus Cy3 system (Perkin Elmer).…”
Section: Methodsmentioning
confidence: 99%
“…miRs are endogenous, short non-coding, single-stranded RNA spanning approximately 22 nucleotides. We and others have shown that radiation regulated miRs alter DNA damage repair pathways, pro-survival signaling pathways, cell-cycle checkpoint regulation, and apoptosis; functions which radiation therapy exploits for therapeutic gain (19)(20)(21)(22)(23)(24). Our previous work identified a group of miRs regulated in the tumor vasculature in response to radiation (25).…”
Section: Introductionmentioning
confidence: 99%